THE REALIZATION OF SPEECH FUNCTION IN ENGLISH CLASSROOM INTERACTION BASED ON SYSTEMIC FUNCTIONAL LINGUISTICS THEORY - Arini Supika; Fahri Haswani (Universitas Negeri Medan, 2018)
This study deals with speech functions used by teacher and students during reading comprehension session in English vocational classroom interaction. The objectives of this study were to find out the types of speech function which were dominantly used by teacher and students and the reasons for the existences of that dominant one. A descriptive qualitative design was used in this study. The data were collected by observing, recording the utterances of teacher and the tenth grade students at SMK Jambi Medan, and by interviewing the subjects. The data were analyzed based on Systemic Functional Linguistics theory. There were 552 clauses produced as the total number where teacher produced 411 clauses and students produced 141 clauses. The results showed that question was the dominant type of speech function used by teacher followed by statement, acknowledgement, command, contradiction and offer. Meanwhile, the dominant type of speech function used by students was answer, followed by compliance, statement, acknowledgement, and disclaimer. The existences of initiating question on the teacher’s performance were affected by the presage category (teacher’s belief) and context category (the class in which the teaching process takes place), while, the existences of answer on the students’ performance were affected by the students’ thought processes category (students’ perception and understanding) and the context category. In conclusion, the teacher used the speech function which focused on using initiation of question, while students dominantly used answer speech function in English classroom interaction.